Phrase Structure Analysis On The Title Of The Headline News In The Jakarta Post Online - Eka Susylowati; Meria Zakiyah Alfisuma; M. Masqotul Imam Romadlani; Zulkhaeriyah Zulkhaeriyah; Luthfi Awwalia (Journal of Social, Culture, and Language, 2024)
The Jakarta Post as one of online media can be used as a media for practicing English. The research is aimed to find what kinds of phrase used in the title of the headline news in the Jakarta Post online and to analyze the phrase construction on the title of the headline news in the Jakarta Post online. A descriptive research method is used in the phrase structure analysis on the title of the headline news in the Jakarta Post online. The data source of the study is obtained from the title of the headline news in the Jakarta Post online from January 2023 to May 2023. In the collecting the data, the writer reads the text then classifies it into phrase based on their types. It is called the documentation. Besides, the writer also used note taking. Method agih used to analyze the data. The result of the research shows that three phrases, namely noun phrase, verb phrase, and gerundive phrase. Keywords: phrase structure, headline news, Jakarta post online